Expression of 120 kilodalton protein and cytotoxicity in Helicobacter pylori. - Crabtree, J. E. (1992)
Antral biopsy culture supernatants from 14 subjects with chronic gastritis, known to have IgA antibodies to the 120 kilodalton protein, showed positive recognition of this antigen in western blots against a cytotoxin positive strain of Helicobacter pylori but gave negative reactions with two cytotoxin negative strains. Control immunoblots with culture supernatants from 13 non-responders to the protein were all negative. This indicates a direct association between expression of the 120 kilodalton protein in H pylori strains and cytotoxicity.